Comparison of the clinicopathological features of flat and polypoid colorectal adenomas that are smaller than or equal to five millimeters - (:unkn) unknown (My University, 2014)
0

Background/Aims: Colorectal flat adenomas (FAs) may represent a different histogenesis, since their malignant potential is thought to be higher than polypoid adenomas of the same size. In this study, we classified FAs of <=5 mm into three subgroups-superficially elevated adenomas (SEAs), completely flat adenomas (CFAs), and depressed adenomas (DAs)based on their low microscopic shapes and compared their clinicopathological features with polypoid tubular adenomas (pTAs) with the same size. Materials and Methods: One hundred one pTAs and 46 FAs with tubular morphology with the same size (<=5 mm) were studied. Results: The percentages of high-grade dysplasia in FAs and pTAs were 19.56% and 12.87%, respectively. The percentages of the high-grade dysplasia were 28.57%, 13.63%, and 20.00% in the DA, SEA, and CFA subgroups, respectively. FAs had a significantly higher number of normal epithelium at the basal crypts of the lesion than the pTAs (p=0.001). The presence of pericryptal mesenchymal cells was higher in pTAs than the FAs (78.21% vs 10.86%) (p<0.001). Conclusion: Flat adenoma represents a distinct type of colorectal adenoma with special histopathological properties-existence of a normal epithelium at the basal crypts, lack of pericryptal mesenchymal cells, and a high percentage of highgrade dysplasia-especially when it has a depressed shape at low magnification.
Keywords: Cerrahi